Acute Detubulation of Ventricular Myocytes Amplifies the Inhibitory Effect of Cholinergic Agonist on Intracellular Ca2+ Transients - Belevych, Andriy E.; Bogdanov, Vladimir; Terentyev, Dmitry A.; Gyorke, Sandor (Frontiers in Physiology, 2021)
Muscarinic receptors expressed in cardiac myocytes play a critical role in regulation of heart function by the parasympathetic nervous system. How structural organization of cardiac myocytes affects regulation of Ca2+ handling by muscarinic receptors is not well defined. Using confocal Ca2+ imaging, patch-clamp techniques and immunocytochemistry we studied the relationship between t-tubule density and cholinergic regulation of intracellular Ca2+ in normal murine ventricular myocytes and in myocytes with acute disruption of the t-tubule system caused by formamide treatment. The inhibitory effect of muscarinic receptor agonist carbachol (CCh, 10 microM) on the amplitude of Ca2+ transients, evoked by field-stimulation in the presence of 100 nM isoproterenol (Iso), a beta-adrenergic agonist, was directly proportional to the level of myocyte detubulation. The timing of the maximal rate of fluorescence increase of fluo-4, a Ca2+-sensitive dye, was used to classify image pixels into the regions functionally coupled or uncoupled to the sarcolemmal Ca2+ influx (ICa). CCh decreased the fraction of coupled regions and suppressed Ca2+ propagation from sarcolemma inside the cell. Formamide-treatment reduced ICa density and decreased sarcoplasmic reticulum (SR) Ca2+ content. CCh did not change SR Ca2+ content in Iso-stimulated control and formamide-treated myocytes. CCh inhibited peak ICa recorded in the presence of Iso by ~20% in both control and detubulated myocytes. Reducing ICa amplitude by up to 40% by changing voltage step levels from 0 to -25 mV decreased Ca2+ transients in formamide-treated but not in control myocytes in the presence of Iso. CCh inhibited CaMKII activity, whereas CaMKII inhibition with KN93 mimicked the effect of CCh on Ca2+ transients in formamide-treated myocytes. We conclude that downregulation of t-tubules, coupled with reduced functional reserve of excitation-contraction coupling, increases sensitivity of Ca2+ release and propagation to muscarinic receptor-mediated inhibition of both ICa and CaMKII activity.